The Role of Supervision in Enhancing the Quality of Islamic Religious Education at Middle School Students - Najamuddin, Andi; Santalia, Indo; Fajrin, Fajrin (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study explores the role of supervision in enhancing the quality of Islamic Religious Education at MTs As'adiyah No. 60 Lattimu, focusing on both educational and da'wah perspectives. The research investigates three main questions: (i) What are the forms of educational supervision implemented at MTs As'adiyah No. 60 Lattimu? (ii) How are da'wah strategies implemented in educational supervision at the school? (iii) What is the role of educational supervision in improving the quality of Islamic Religious Education? A qualitative approach was used, involving in-depth interviews, observations, and document analysis. The research findings reveal that supervision significantly contributes to improving education quality through guiding teachers in teaching methods, media usage, and problem-solving strategies. The study shows that the supervision program adheres to principles and characteristics of clinical supervision, ensuring a significant impact on the educational process. Thus, the role of supervision in this context is vital for enhancing the quality of Islamic Religious Education at MTs As'adiyah No. 60 Lattimu.